PERBEDAAN ANTARA SEBELUM DAN SESUDAH PENGUMUMAN RIGHT ISSUE TERHADAP ABNORMAL RETURN DAN TRADING VOLUME ACTIVITY PADA PERUSAHAAN PUBLIK DI BURSA EFEK JAKARTA - Widaryanti . (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2006)
Right issue is once of corporate action in Stock Exchange. This nnouncement is very important for investor to make decision for invesment in public companies.This study aimed to examines the difference Abnormal return mean and Trading Volume Activity mean, before and after righ issue event. Samples in this study are public companies that list in Jakarta Stock Exchange within 2000 – 2003. This research uses 25 public companies which was representatif sampel. With signifikan level 0.05, this research indicates that there is not a difference Abnormal return mean and Trading Volume Activity mean, before and after right issue event. This means that no information in right issue event